Library mesenger, July - December 2015 (Confluenţe Bibliologice, 2015)
This article reflects the most significant activities carried out within the USARB Scientific Library from July to December 2015.
Keywords: Open Access Week; scientific-practical conferences; Departmental Librarianship Center